CORRELATION BETWEEN STRESS AND ANXIETY AMONG NURSES WORKING IN INTENSIVE CARE UNITS OF NISHTAR HOSPITAL, MULTAN: A CROSS-SECTIONAL STUDY (Journal of Medical & Health Sciences Review, 2025)
Objective: Nurses in intensive care units (ICUs) face a demanding work environment that may lead to heightened stress and anxiety. This study aimed to assess the relationship between stress and anxiety among ICU nurses at Nishtar Hospital, Multan.Methods: A cross-sectional correlational study was conducted over a three-month period with 50 ICU nurses selected through purposive sampling. Data were collected using the Perceived Stress Scale (PSS-10) and the Generalized Anxiety Disorder Scale (GAD-7). Descriptive statistics and Pearson’s correlation analysis were performed using SPSS v26.Results: The majority of participants were female (86%) with a mean age of 30.2±5.6 years. Moderate to high stress levels were found in 68% of nurses, while 48% reported moderate to severe anxiety symptoms. Pearson’s correlation revealed a significant positive relationship between stress and anxiety (r=0.62, p